Left Behind : Chronic Poverty in Latin America and the Caribbean - Vakis, Renos; Rigolini, Jamele; Lucchetti, Leonardo (2015)
One out of every five Latin Americans—about 130 million people—have never known anything but poverty, subsisting on less than US$4 a day throughout their lives. These are the region's chronically poor, who have remained so despite unprecedented inroads against poverty in Latin America and the Caribbean since the turn of the century. This book takes a closer look at the region’s entrenched poor, who and where they are, and how existing policies need to change to effectively assist the poor. The book shows significant variations of rates of chronic poverty across and within countries. The book posits that refinements to the existing policy toolkit —as opposed to more programs—may come a long way in helping the remaining poor. These refinements include intensifying efforts to improve coordination between different social and economic programs, which can boost the income-generation process and deal with the intergenerational transmission of chronic poverty by investing in early childhood development. In addition, there is an urgent need to adapt programs to directly address the psychological toll of chronic poverty on people’s mindsets and aspirations, which currently undermines the effectiveness of existing policy efforts.